2017
DOI: 10.21037/jtd.2017.03.12
|View full text |Cite
|
Sign up to set email alerts
|

Transcutaneous electrical acupoint stimulation (TEAS) ameliorates chemotherapy-induced bone marrow suppression in lung cancer patients

Abstract: Background:To investigate the effect of percutaneous electrical stimulation on chemotherapy-induced bone marrow suppression in patients with lung cancer.Methods: From December 2014 to August 2015, one hundred ninety-one non-small cell lung cancer patients with chemotherapy naive were randomly divided into control group, medication group, and transcutaneous electrical acupoint stimulation (TEAS) group. Patients with the control group received routine nursing care, the medication group was treated by oral admini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 9 publications
0
17
1
Order By: Relevance
“…Some studies [ 20 ] suggested that simultaneous stimulation at BL17, SP6, and LI4 can be used for the treatment of primary thrombocytopenic purpura, which could significantly improve the clinical symptoms of patients and promote recovery of platelet counts. Electrical acupoint stimulation at SP6 can nourish the Yin and blood.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies [ 20 ] suggested that simultaneous stimulation at BL17, SP6, and LI4 can be used for the treatment of primary thrombocytopenic purpura, which could significantly improve the clinical symptoms of patients and promote recovery of platelet counts. Electrical acupoint stimulation at SP6 can nourish the Yin and blood.…”
Section: Discussionmentioning
confidence: 99%
“…Points ST-36 and SP-6 together with points DU-14 (Dazhui), BL-14 (Geshu), and LI-14 (Hegu) according to Hou et al [15] can reduce bone marrow suppression and be able to enrich the blood, especially an increase in total leukocytes. This study did not show a significant effect on the increase in erythrocytes in patients with myelosuppression due to the use of chemotherapy drugs.…”
Section: Discussionmentioning
confidence: 99%
“…The sample used was 191 patients with 52 patients in the acupuncture treatment group. Hou et al [15] said that to get results in the form of an increase in total erythrocyte and haemoglobin, it would be better to increase the sample size and extend the frequency or repetition of acupuncture such as more than 120 days.…”
Section: Discussionmentioning
confidence: 99%
“…The main objective of the SR is to evaluate the efficacy and safety of acupuncture for chemotherapy induced marrow suppression; therefore, the primary outcomes are as follows: white blood cell (WBC) counts, [ 24 ] platelet counts, [ 25 ] hemoglobin counts, [ 26 ] or other validated outcome measures.…”
Section: Methodsmentioning
confidence: 99%